Mapping of contact sites in complex formation between transducin and light-activated rhodopsin by covalent crosslinking: Use of a photoactivatable reagent - Cai, Kewen (The National Academy of Sciences, 2001)
Interaction of light-activated rhodopsin with transducin (T) is the first event in visual signal transduction. We use covalent crosslinking approaches to map the contact sites in interaction between the two proteins. Here we use a photoactivatable reagent, N-[(2-pyridyldithio)-ethyl], 4-azido salicylamide. The reagent is attached to the SH group of cytoplasmic monocysteine rhodopsin mutants by a disulfide-exchange reaction with the pyridylthio group, and the derivatized rhodopsin then is complexed with T by illumination at λ >495 nm. Subsequent irradiation of the complex at λ310 nm generates covalent crosslinks between the two proteins. Crosslinking was demonstrated between T and a number of single cysteine rhodopsin mutants. However, sites of crosslinks were investigated in detail only between T and the rhodopsin mutant S240C (cytoplasmic loop V-VI). Crosslinking occurred predominantly with T(α). For identification of the sites of crosslinks in T(α), the strategy used involved: (i) derivatization of all of the free cysteines in the crosslinked proteins with N-ethylmaleimide; (ii) reduction of the disulfide bond linking the two proteins and isolation of all of the T(α) species carrying the crosslinked moiety with a free SH group; (iii) adduct formation of the latter with the N-maleimide moiety of the reagent, maleimido-butyryl-biocytin, containing a biotinyl group; (iv) trypsin degradation of the resulting T(α) derivatives and isolation of T(α) peptides carrying maleimido-butyryl-biocytin by avidin-agarose chromatography; and (v) identification of the isolated peptides by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. We found that crosslinking occurred mainly to two C-terminal peptides in T(α) containing the amino acid sequences 310–313 and 342–345.